Microstructure transformation of deformed AZ91D during isothermal holding - 张友法 刘勇兵 曹占义 张亮 (Transactions of Nonferrous Metals Society of China, 2010)
In order to understand the thermodynamic properties of deformed AZ91D alloy during isothermal holding, the microstructure characteristics and transformation were investigated. The results present that deformation mainly concentrates on the edge of the chips and billets, especially at the interface of α/β. Microstructure transformation mechanism of deformed AZ91D during holding mainly includes recrystallization, spheroidization and Ostwald ripening. The mechanism was then thermodynamically analyzed. During the heating and isothermal holding process, recrystallization driven by residual energy within the deformed AZ91D alloy, spheroidization and Ostwald ripening induced by the reduction of interracial energy, will inevitably and continuously occur with the extension of heating and holding.